The influence of exploitative management style on student learning outcomes in public higher education institutions of Cambodia: Faculty development initiatives as a mediator - Holl, Piseth; Ali, Dhakir Abbas (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of exploitative management style (EMS) on student learning outcomes (SLOs) in Cambodian public higher education institutions, with faculty development initiatives (FDIs) analyzed as a mediating factor. A quantitative approach was employed, using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze responses from 305 lecturers across selected public universities. Validated constructs were applied to measure EMS, FDIs, and SLOs, ensuring reliability and validity. The structural model reveals that EMS significantly influences both SLOs (β = 0.220, t = 4.108, p = 0.000) and FDIs (β = 0.426, t = 9.945, p = 0.000). FDIs, in turn, significantly enhance SLOs (β = 0.382, t = 6.539, p = 0.000) and partially mediate the relationship between EMS and SLOs (β = 0.163, t = 5.506, p = 0.000). The model explains 18.0% of the variance in FDIs and 26.4% in SLOs, with acceptable predictive relevance and fit. EMS positively affects SLOs both directly and indirectly through FDIs, indicating that, within structured academic environments, EMS contributes positively by fostering clarity, discipline, and targeted faculty development. The study highlights the importance of strategically aligning management practices with faculty development programs to strengthen student learning outcomes in resource-constrained higher education contexts.